Clinical Profile of Haemophilia In Children in A Tertiary Care Hospital - Karim, MA; Siddique, R; Jamal, CY; Islam, A (Bangladesh Journal of Child Health, 2013)
Introduction : Haemophilias are the most common inherited coagulation disorders transmitted by X- linked recessive fashion affecting the males and females are the carriers of the disease. Haemophilias are distributed worldwide and have heterogeneous presentation depending upon its severity starting from neonatal period. Knowledge of spectrum of presentation of haemophilia helps in early diagnosis and planning of management. Objectives : To observe the clinical presentation of haemophilia in children Methodology : This observational study was carried out in the Department of Pediatric Hematology and Oncology, Bangabandhu Sheikh Mujib Medical University for a period of one year from 1st July 2007 to 30th June 2008. Clinical profile of 50 diagnosed cases of haemophilia <15 years of age was analyzed. Result: All the 50 cases of haemophilia were male. Mean age of the patients was 6.62±3.87 years with an age range of 6 months to 14 years. Forty (80%) cases were haemophilia A and 10 (20%) cases were Haemophilia B. Only 40% cases had family history of bleeding. Among the Haemophilia A, 52.5% cases had mild, 47.5% cases had moderate disease and among the Haemophilia B, 40% cases had mild, 50% cases had moderate and 10% cases had severe disease. Heamarthrosis of knee joint was the major presentation followed by oral cavity bleeding, bleeding following tooth extraction and circumcision. Sixty two percent cases had initial bleeding episode before 1 year of age and by 5 years of age 94% of cases had produced symptoms. No patient had history of bleeding during neonatal period. Bruises and hematoma were the most common initial manifestation followed by joint bleeding, cut injury of lips and chin, scalp and facial hematoma. Conclusion: Bruises, hematoma and joint bleeding either spontaneous or after trauma were the main feature at initial presentation of haemophilia in children, so presence of these features in an otherwise normal child should be considered for evaluation of haemophilia. More vigilance is to be needed for detection of haemophilia in newborn. DOI: http://dx.doi.org/10.3329/bjch.v37i2.17266 BANGLADESH J CHILD HEALTH 2013; VOL 37 (2) : 90-96